Factorise fully the following:
25x²-16y²
2x²-5xy²-3y²
TPS:
second one is 2x²-5xy-3y² or 2x²-5xy²-3y²??
Answers
Answered by
0
25x² - 16y²
= (5x)² - (4y)²
= (5x+4y)(5x-4y)
---------------------------------
2x² - 5xy - 3y²
= 2x² - 6xy + xy - 3y²
= 2x(x-3y) + y(x - 3y)
= (x-3y)(2x+y)
= (5x)² - (4y)²
= (5x+4y)(5x-4y)
---------------------------------
2x² - 5xy - 3y²
= 2x² - 6xy + xy - 3y²
= 2x(x-3y) + y(x - 3y)
= (x-3y)(2x+y)
Answered by
0
1)
25x² - 16y²
⇒(5x)² - (4y)²
⇒ (5x + 4y)(5x - 4y) [Using the formula a² - b² = (a +b)(a-b)
2) I think, the question should be
2x²-5xy-3y²
⇒2x² - 6xy + xy - 3y²
⇒ 2x(x - 3y) + y(x - 3y)
⇒ (x - 3y)( 2x + y)
25x² - 16y²
⇒(5x)² - (4y)²
⇒ (5x + 4y)(5x - 4y) [Using the formula a² - b² = (a +b)(a-b)
2) I think, the question should be
2x²-5xy-3y²
⇒2x² - 6xy + xy - 3y²
⇒ 2x(x - 3y) + y(x - 3y)
⇒ (x - 3y)( 2x + y)
Similar questions